Vaughan Williams and the soundscapes of Scott of the Antarctic - Philpott, C; Leane, E; Quin, D (The Musical Quarterly, 2020)
Vaughan Williamss music for the 1948 Ealing Studios production Scott of the Antarctic hasbeen recognized as one of the most outstanding film scores of its time. However, to date, ithas received considerably less scholarly attention than the much more famous work itgerminated, the Sinfonia Antartica (194952). While there have been some discussions of the film score within larger surveys of the composers oeuvre, these have not investigated the music to quite the same level of depth as that achieved in the separate studies of the Sinfonia Antartica undertaken by Michael Beckerman and Daniel Grimley. This lacuna is consistent,however, with the general treatment of Vaughan Williamss film scores, which have tendedto be overlooked or only addressed in passing in the scholarly literature.